OPINION ANALYSIS GOING CONCERN THROUGH AUDITOR QUALITY AND AUDITOR EXPERIENCE - Wulandari, Retno; Nuryana, Ida (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
The research was conducted in Malang City area with auditor as the population while the sample with pursposive sampling while the data analysis used is variable test with linkert scale and using SPPS statitisk test. In this study conducted at the Public Accounting Firm in Malang, showed that by using validity test, reliability, assumption Heterokedastisitas, multicolinierity assumption test, hypothesis testing simultaneously and partial and autocorrelation test showed that the questionnaire used by the researchers is feasible as a measuring tool for analysis in this study and provide consistent results. In the test results Hypothesis gives results that reject Ho and accept the hypothesis of research Ha, so that the auditor experience and audit quality together provide a significant effect on going concern opinion. Partial experience does not affect the giving of going concern opinion while the quality of audit partially affect the giving of going concern opinion.